1999
DOI: 10.1093/carcin/20.9.1877
|View full text |Cite
|
Sign up to set email alerts
|

NAT2 slow acetylator genotype is associated with increased risk of lung cancer among non-smoking Chinese women in Singapore

Abstract: Among non-smokers, the factors resulting in lung carcinogenesis are poorly understood. We conducted a hospital-based case-control analysis of 294 Chinese women, of whom 217 were non-smokers, to evaluate the role of polymorphic N-acetyltransferase (NAT2) as a susceptibility factor for the disease. The proportion of slow acetylator genotypes among non-smoking cases (n = 92) and controls (n = 125) was 38.0 and 24.0%, respectively [odds ratio (OR) 2.0, 95% confidence interval (CI) 1.1-3.7]. No effect of NAT2 genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 30 publications
3
46
1
2
Order By: Relevance
“…Nevertheless, authors seem to confirm a modulatory effect of smoking status on NAT2-associated lung cancer risk (Table 8). While in non-smokers, the slow acetylator phenotype determining genotypes seem to be associated with increased risk of lung cancer, among smokers, such genotypes are rather protective [133,134]. In consent with this seems to be the conclusion, that the fast acetylator genotypes comprise a risk factor for heavy smokers (OR = 1.22; 95% CI: 0.89-1.67), while provide protection against lung cancer among nonsmokers (OR = 0.66; 95% CI: 0.79-1.16).…”
Section: N-acetyltransferasesmentioning
confidence: 99%
“…Nevertheless, authors seem to confirm a modulatory effect of smoking status on NAT2-associated lung cancer risk (Table 8). While in non-smokers, the slow acetylator phenotype determining genotypes seem to be associated with increased risk of lung cancer, among smokers, such genotypes are rather protective [133,134]. In consent with this seems to be the conclusion, that the fast acetylator genotypes comprise a risk factor for heavy smokers (OR = 1.22; 95% CI: 0.89-1.67), while provide protection against lung cancer among nonsmokers (OR = 0.66; 95% CI: 0.79-1.16).…”
Section: N-acetyltransferasesmentioning
confidence: 99%
“…Studies have been conflicting with regard to the association with lung cancer risk. Most studies report no overall increase in risk with either the slow or fast acetylators (Philip et al, 1988;Martinez et al, 1995;Bouchardy et al, 1998;Saarikoski et al, 2000), whereas a few have reported increased risk with either the slow (Oyama et al, 1997;Seow et al, 1999) or fast acetylator genotype. In the largest study of 1115 lung cancer patients and 1250 controls, no association was found between the NAT2 genotype and lung cancer risk (Zhou et al, 2002b).…”
Section: Carcinogen Metabolismmentioning
confidence: 99%
“…Individuals, with combined NAT1 rapid and NAT2 slow genotype, seemed to have a significantly higher risk for lung adenocarcinoma (23), or the NAT2 slow genotype when combined with the GSTM1-null genotype may increase the susceptibility to adduct formation, gene mutation, and lung cancer risk (24). Similarly, a combination of NAT2 slow/CYP1A1 rapid acetylator may also predispose higher risk to lung cancer in nonsmoking females (11). Although there is no single polymorphism able to predict the risk of brain tumors, an allelic combination could jointly affect the risk of brain tumors (13,25).…”
Section: Discussionmentioning
confidence: 99%
“…Slow acetylator phenotypes caused by polymorphisms in NAT2 gene confer a higher risk of bladder cancer due to the reduced activity in the hepatic N-acetylation pathway, which detoxifies compounds such as 4-aminobiphenyl and competes with N-oxidation of these compounds by cytochrome P4501A2 to reactive hydroxylamines. The relationship between the polymorphism of NAT2 and other cancers such as lung and colorectal cancer has also been studied (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%